Do the diagnosis-related group payment reforms have a negative impact?—an empirical study from Western China - Wang, Jia-Yi; Chen, Meng-En; Wei, Xue-Xuan; Lu, Xi-Zhu; Zhu, Yuan-Rui; Yang, Jing-Yu (Frontiers in Public Health, 2025)
BackgroundThe first Diagnosis-Related Group (DRG) Reimbursement pilots in China, which started in 2019, marked an essential step in cost control and service efficiency in Chinese hospitals, but some adverse effects inevitably emerged during the implementation of DRG in TCM (traditional Chinese medicine) hospitals. This study aims to explore the positive and negative effects of DRG payment reform and provide a reference for the reform of medical insurance payments in countries that retain traditional medicine.MethodsLongitudinal data from two hospitals, Qingyang City Hospital of TCM and Tianshui City Hospital of TCM, were retrieved from China’s Gansu Health for All Big Data Platform from June 2016 to June 2022, and the policy effects were assessed using the difference-in-differences (DID) method and mediated-effects model.ResultsThe DRG reform reduced hospitalization costs, diagnostic costs, drug costs, and nursing costs by 6.5, 4.2, 7.9, and 26.2%, respectively, in the treatment group hospitals (p < 0.01), but increased the hospitalization times by 17.5% (p < 0.01); there was a “reimbursement bias” for patients with different types of medical insurance. In the treatment group hospitals, the primary beneficiaries of the reform were urban employees’ basic medical insurance patients, whose costs decreased by 4.9% (p < 0.01), with a non-significant effect on out-of-pocket payment patients and free medical care patients; the hospitals in the treatment group tended to reduce the use of Chinese medicine unique diagnostic and therapeutic means and increase the proportion of western medicine treatments under the pressure of the supremacy of costs.ConclusionThe reform of the DRG payment method has positively impacted the cost control of TCM hospitals, but it has also had some adverse effects. This poses a challenge and prompts a thought about how TCM hospitals can maintain their distinctive advantages by optimizing the design of the DRG system at present.